PENEGAKAN HUKUM HUMANITER DALAM KONFLIK BERSENJATA INTERNAL SURIAH - Harry Japmika, I Wayan Gede; Pasek Diantha, I Made; Budi Arsika, I Made (Kertha Negara : Journal Ilmu Hukum; Vol. 02, No. 03, Mei 2014)
The leadership of Syrian President, Bashar al-Assad was under pressure from Syrian people who performed demonstrations demanding him to retreat from the power. The reaction of the Syrian government ordered its military forces to execute repressive measures against the demonstrators has turned out the demonstrations into an armed conflict between the government and belligerent. This paper will reveal the  constraints of the humanitarian law enforcement on the internal armed conflict occurred in Syria and will also analyze the kinds of sanctions that may be imposed on the parties to the dispute in the conflict. This paper is a normative legal research that uses several approaches namely statutory approach, facts approach, analytical-legal  conceptual approach, and historical approach.
Keywords: Internal armed conflict, Humanitarian law, Syria